New insight on microglia activation in neurodegenerative diseases and therapeutics - Xu, Yucong; Gao, Wei; Sun, Yingnan; Wu, Minghua (Frontiers in Neuroscience, 2023)
Microglia are immune cells within the central nervous system (CNS) closely linked to brain health and neurodegenerative diseases such as Alzheimer's Disease and Parkinson's disease. In response to changes in the surrounding environment, microglia activate and change their state and function. Several factors, example for circadian rhythm disruption and the development of neurodegenerative diseases, influence microglia activation. In this review, we explore microglia's function and the associated neural mechanisms. We elucidate that circadian rhythms are essential factors influencing microglia activation and function. Circadian rhythm disruption affects microglia activation and, consequently, neurodegenerative diseases. In addition, we found that abnormal microglia activation is a common feature of neurodegenerative diseases and an essential factor of disease development. Here we highlight the importance of microglia activation in neurodegenerative diseases.Targeting microglia for neurodegenerative disease treatment is a promising direction.We introduce the progress of methods targeting microglia for the treatment of neurodegenerative diseases and summarize the progress of drugs developed with microglia as targets, hoping to provide new ideas for treating neurodegenerative diseases.